2022
DOI: 10.1096/fba.2021-00152
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a long‐term high‐fructose diet on systemic metabolic profiles of mice

Abstract: Evidence is mounting that chronic high‐fructose diets (HFrD) can lead to metabolic abnormalities and cause a variety of diseases. However, the underlying mechanism by which long‐term high fructose intake influencing systemic metabolism remains unclarified. This study, therefore, attempted to investigate the impact of a high‐fructose diet on metabolic profile. Four‐week‐old male C57BL/6 mice were fed with 15% fructose solution as their only source of water for 8 weeks. Afterward, gas chromatography–mass spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…A growing number of studies have shown that metabolites play crucial roles in physiological and pathological aging. Aging and dietary interventions cause changes in metabolites, and alterations in metabolites and metabolic pathways can help to elucidate the mechanisms of diseases or treatments (33). In addition, changes in multiple metabolites have been associated with oxidative stress and inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of studies have shown that metabolites play crucial roles in physiological and pathological aging. Aging and dietary interventions cause changes in metabolites, and alterations in metabolites and metabolic pathways can help to elucidate the mechanisms of diseases or treatments (33). In addition, changes in multiple metabolites have been associated with oxidative stress and inflammation.…”
Section: Introductionmentioning
confidence: 99%